2021
DOI: 10.3390/toxins14010003
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated Effects of Allyl Isothiocyanate in Diabetic Rats: From Toxic to Beneficial Action

Abstract: Allyl isothiocyanate (AITC), a constituent of Brassica family plants, has been reported to possess a high bioactivity in animal and human cells, showing ambiguous properties from adverse to beneficial ones. It was reported its genotoxic, carcinogenic, goitrogenic effects. On the other side, AITC has shown anti-cancer, cardioprotective, neuroprotective, and lately anti-obesity abilities. So far, its anti-diabetic effects are poorly explored. We tried to assess AITC action on carbohydrate, lipid and hormonal dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…36 Although, diagnostic and surgical techniques improved the survival rate in patients with gastric cancer but still unsatisfied, limited therapeutic effects, therefore, more important to identify targets or markers or selected compounds from natural products for improved therapeutic efficacy in patients with gastric cancer that are required. Recently, it is well documented that AITC presents pharmacological effects including anticancer activities, [20][21][22][23][24][25][26][27][28][29][30] however, slightly to address induced DNA damage, thus, we investigate AITC-induced cell death whether or not through the effects of DNA damage and repair associated proteins in gastric cancer. We selected two gastric cancer cell lines (AGS and SNU-1) for the whole studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…36 Although, diagnostic and surgical techniques improved the survival rate in patients with gastric cancer but still unsatisfied, limited therapeutic effects, therefore, more important to identify targets or markers or selected compounds from natural products for improved therapeutic efficacy in patients with gastric cancer that are required. Recently, it is well documented that AITC presents pharmacological effects including anticancer activities, [20][21][22][23][24][25][26][27][28][29][30] however, slightly to address induced DNA damage, thus, we investigate AITC-induced cell death whether or not through the effects of DNA damage and repair associated proteins in gastric cancer. We selected two gastric cancer cell lines (AGS and SNU-1) for the whole studies.…”
Section: Discussionmentioning
confidence: 99%
“…17 ITCs may suppress oncogenesis and tumor progression 18 and it may diminish the risk of bladder cancer recurrence. 19 Numerous preclinical studies have shown that AITC has pharmacological activities such as antimicrobial, 20 antioxidant, 21 chemoprevention, [22][23][24] antiobesity, 25,26 anti-inflammatory, 27,28 and anticancer 29,30 activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this compound can protect organs and tissues against various toxins [ 6 , 98 ]. This is a relevant feature since some compounds may have contradictory action, alleviating diabetes-related changes at lower doses and aggravating them at higher doses [ 99 , 100 ].…”
Section: Effective Doses and Toxicitymentioning
confidence: 99%
“…Elevated Cu/Zn ratios are associated with oxidative stress, inflammation, and disrupted immune status [ 21 ]. Recently, we have shown that AITC affects hormone levels and metabolic status in diabetic rats [ 22 ]. However, there are no sufficient data on the influence of this compound on oxidative and inflammatory stress in rats with experimentally induced diabetes.…”
Section: Introductionmentioning
confidence: 99%